Motor Vehicle Tax Amnesty and Transfer Fee Exemption on Taxpayer Compliance: The Moderating Role of Tax Socialization - Nataullah Zilan Utami; Ardan Gani Asalam (FOUNDAE (Foundation of Advanced Education), 2026)
Motor vehicle tax and motor vehicle ownership transfer fee are important sources of local own-source revenue. However, low taxpayer compliance constrains the optimization of regional revenue. This study examines the effects of motor vehicle tax amnesty and motor vehicle ownership transfer fee exemption on motor vehicle taxpayer compliance, with tax socialization as a moderating variable. This study used a quantitative approach involving 113 respondents selected through incidental sampling. The data were analyzed using multiple linear regression to test the direct effects and Moderated Regression Analysis (MRA) to examine the moderating effect of tax socialization. The results show that motor vehicle tax amnesty has a positive and significant effect on taxpayer compliance (p = 0.029), and motor vehicle ownership transfer fee exemption also has a positive and significant effect on taxpayer compliance (p = 0.003). Furthermore, tax socialization weakens the effect of motor vehicle tax amnesty on taxpayer compliance (p = 0.025), but strengthens the effect of motor vehicle ownership transfer fee exemption on taxpayer compliance (p = 0.018). These findings indicate that tax socialization plays different moderating roles across tax incentive policies. Therefore, tax authorities should adjust their communication strategies according to the characteristics of each incentive policy to improve taxpayer compliance.